Impact of clinicopathological factors on extended endocrine therapy decision making in estrogen receptor–positive breast cancer - Chen, Weilin; Wu, Jiayi; Zhu, Yifei; Huang, Jiahui; Chen, Xiaosong; Huang, Ou; He, Jianrong; Li, Yafen; Chen, Weiguo; Shen, Kunwei; Zhu, Li (Frontiers in Oncology, 2023)
Purpose: In our study, we aim to analyze the impact of clinicopathological factors on the recommendation of extended endocrine therapy in patients with ER+ breast cancer and to retrospectively validate the value of CTS5 in EET decision-making. Patients and Methods: The retrospective analysis was performed in patients with ER-positive breast cancer who have finished 4.5-5 years of adjuvant endocrine therapy and undergone MDT discussion from October 2017 to November 2019. Multivariate logistic regression was used to identify the independent factors for treatment recommendation. CTS5 was calculated for retrospective validation of the EET decision-making. Results: 235 patients who was post-surgery and had received 4.5-5 years of adjuvant endocrine therapy were included in the study. Multivariate analysis suggested that age (OR 0.460, 95% CI 0.219-0.965, p=0.04), pN (OR 39.350, 95% CI 9.831-157.341, P<0.001) and receipt of chemotherapy (OR 3.478, 95% CI 1.336-9.055, p=0.011) were independent predictors for recommendation of EET. In the previously-SERM subgroup, pN and receipt of chemotherapy were independent predictors for recommendation of EET and in the previously-AI subgroup, age, pN and receipt of chemotherapy were its independent predictors. Adverse events didn’t affect the recommendation in patients previously treated with adjuvant endocrine treatment, nor in the previously-SERM or AI-treated subgroups. CTS5(OR 21.887, 95% CI 2.846-168.309, p=0.003) remained an independent predictor for recommendation of EET. Conclusion: Our study indicated that age, lymph nodal status and receipted of chemotherapy were independent predictors for recommendation of EET. The application of the CTS5 on EET decision-making might be valuable among ER+ breast cancer patients.